Ответы и объяснения

2014-01-13T18:51:25+04:00
75 - 5Х = 30    
-5х=30-75
-5х= -45
х= -45:(-5)
х=9

93 - 3Х = 392 -311
-3х=392-311-93
-3х= -12
х= -12: (-3)
х=4
( 25 + 8)Х = 99
х(58- 27) = 62
25х+8х=99; 33х=99; х=99:33; х=3
58х-27х=62; 31х=62; х=62:31; х=2
2014-01-13T18:54:06+04:00
75-5Х=30                                                                                                                   75-5*Х=30                                                                                                                  5*Х=75+30                                                                                                                5*Х=105                                                                                                                    Х=105:5                                                                                                                    Х=21